2006
DOI: 10.1001/archpsyc.63.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Cocaine Craving and Hypothalamic-Pituitary-Adrenal Responses Are Predictive of Cocaine Relapse Outcomes

Abstract: These results demonstrate that stress-related increases in cocaine craving and hypothalamic-pituitary-adrenal axis responses are each associated with specific cocaine relapse outcomes. The findings support the use of stress-induced drug craving and associated hypothalamic-pituitary-adrenal axis responses to evaluate cocaine relapse propensity. Furthermore, treatments that address stress-induced cocaine craving and hypothalamic-pituitary-adrenal responses could be of benefit in improving relapse outcomes in coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
390
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 488 publications
(418 citation statements)
references
References 50 publications
21
390
3
4
Order By: Relevance
“…Stressful imagery has been reported to elicit drug craving in abstinent cocaine users (Fox et al, 2005). Moreover, using the same procedure, an inverse relationship between stress-induced cocaine craving and time to relapse, as well as a positive relationship between stress-induced cortisol levels and drug intake, during relapse, has been reported (Sinha et al, 2006). Data from animal models of relapse also support the importance of stress in reinstating previously extinguished drug-seeking behavior (see Shaham et al, 2000 for a review) and, in the case of heroin, rats with long (11-h) access exhibit greater levels of stress-induced reinstatement compared to those with short (1-h) access (Ahmed et al, 2000).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Stressful imagery has been reported to elicit drug craving in abstinent cocaine users (Fox et al, 2005). Moreover, using the same procedure, an inverse relationship between stress-induced cocaine craving and time to relapse, as well as a positive relationship between stress-induced cortisol levels and drug intake, during relapse, has been reported (Sinha et al, 2006). Data from animal models of relapse also support the importance of stress in reinstating previously extinguished drug-seeking behavior (see Shaham et al, 2000 for a review) and, in the case of heroin, rats with long (11-h) access exhibit greater levels of stress-induced reinstatement compared to those with short (1-h) access (Ahmed et al, 2000).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, increased and persistent stress reactivity associated with a history of escalated cocaine self-administration suggests that increased sensitivity to stress induced by chronic cocaine may exacerbate the role of stress per se as a risk factor for relapse. Moreover, because stress also induces craving (Fox et al, 2005), a condition that has been shown to be predictive of shorter time to relapse and increased drug intake during relapse (Sinha et al, 2006), increased stress reactivity may further exacerbate the likelihood and severity of relapse associated with cocaine craving.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even after a period of abstinence, dependent individuals remain vulnerable to stress and other craving-inducing stimuli [10], which, in turn, leads to intense physiological responses and various negative feelings such as anger and sadness [11]. Real-time daily monitoring of craving and drug use has shown that craving reliably predicts relapse among dependent individuals [9,[12][13][14][15]. The data suggest that improving the treatment of craving could not only help prevent relapse, but could also reduce patient distress on the emotional, cognitive, and physiological levels.…”
Section: Overview Of Addiction and Current Treatment Challengesmentioning
confidence: 99%
“…However, other clinical studies have reported that after a brief period of abstinence, basal and corticotropin-releasing factor (CRF)-stimulated ACTH and cortisol levels in cocaine-dependent patients do not differ from those of healthy subjects (Mendelson et al, 1998;Jacobsen et al, 2001;Aouizerate et al, 2006). Psychological stressors or CRF elevate cocaine craving and HPA activity, and stress-induced ACTH and cortisol responses predict subsequent cocaine relapse (Sinha et al, 2006;Brady et al, 2009).…”
Section: Introductionmentioning
confidence: 99%